Educational Innovations for Sustainable Learning in Higher Education: A Systematic Literature Review - Ali Mujahidin; Budi Irawanto; Rika Pristian Fitri Astuti (Proceeding International Conference on Digital Education and Social Science, 2025)
Higher education plays a vital role in supporting the social, economic, and cultural development of global societies. With the advancement of technology and increasing global demands, higher education institutions are required to continuously innovate in order to create relevant and sustainable learning experiences. This study aims to systematically review various educational innovations implemented in higher education to support sustainable learning. Using a PRISMA-based Systematic Literature Review (SLR) approach, 37 articles published between 2020 and 2024 were analyzed. The study identified three main categories of educational innovation: curriculum innovation, instructional innovation, and educational technology innovation. Curriculum innovations include the integration of sustainability principles and the development of 21st-century skills. Instructional innovations involve active learning approaches and personalized learning technologies. Meanwhile, technological innovations focus on the use of AI, AR/VR, and digital learning platforms that enhance interactive and inclusive learning experiences. Despite challenges such as infrastructure gaps, limited faculty training, and unequal access to technology, this study highlights the importance of integrated and sustainable approaches in implementing educational innovations. It provides evidence-based recommendations for higher education institutions to develop more relevant, inclusive, and sustainable learning practices.